Load-Bearing Capacity of Podium Frame for Translucent Atrium Roof - Aleksandra R. Masenene; Sergey V. Klyuev (Structural Mechanics of Engineering Constructions and Buildings)
The object of the study is the strength and load-bearing capacity of an element of a translucent atrium roof with a podium frame made of glass composite filled with foam glass. Mechanical tests were carried out on a full-scale sample using specialized equipment to study the joint operation of the load-bearing steel structure, roof element and element fastening. The test method for determining load-bearing capacity is based on the method of static compression testing of a multilayer composite material. The test was carried out in laboratory conditions using certified equipment. The following parameters were tracked during the tests: load, deformation behavior, and deflection of the sample. The test was carried out until the sample was destroyed. Results. The load-bearing capacity of the podium frame made of fiberglass has been determined. A graph of the relationship between deformation (deflection) of the element and the load was obtained. The tests confirmed the possibility of using a podium frame made of glass composite filled with foam glass for a translucent atrium roof. The load-bearing capacity significantly exceeds the design loads during operation. The characteristics of failure of the fastening locations in the structure were obtained. Strengthening the fastening holes of the structure can be considered as one of the promising areas for further research. The directions for future studies of the element of the translucent atrium roof made of glass composite filled with foam glass are considered.